2020
DOI: 10.1021/acs.macromol.9b02428
|View full text |Cite
|
Sign up to set email alerts
|

Kremer–Grest Models for Commodity Polymer Melts: Linking Theory, Experiment, and Simulation at the Kuhn Scale

Abstract: The Kremer–Grest (KG) polymer model is a standard model for studying generic polymer properties in molecular dynamics simulations. It owes its popularity to its simplicity and computational efficiency, rather than its ability to represent specific polymers species and conditions. Here we show that by tuning the chain stiffness it is possible to adapt the KG model to model melts of real polymers. In particular, we provide mapping relations from KG to SI units for a wide range of commodity polymers. The connecti… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
207
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 138 publications
(213 citation statements)
references
References 151 publications
6
207
0
Order By: Relevance
“…The fully flexible chain consists of purely repulsive Lennard-Jones beads and a harmonic bond known to reproduce the same chain structures as finitely extensible (FENE) bonds. This, along with a reported characteristic ratio of C ∞ = 2.1, makes it very similar to the standard Kremer-Grest (KG) model (C ∞,KG = 1.7) [41,42]. We thus refer to it as a KG-like chain.…”
Section: Comparison With Different Modelsmentioning
confidence: 53%
“…The fully flexible chain consists of purely repulsive Lennard-Jones beads and a harmonic bond known to reproduce the same chain structures as finitely extensible (FENE) bonds. This, along with a reported characteristic ratio of C ∞ = 2.1, makes it very similar to the standard Kremer-Grest (KG) model (C ∞,KG = 1.7) [41,42]. We thus refer to it as a KG-like chain.…”
Section: Comparison With Different Modelsmentioning
confidence: 53%
“…Thermodynamic Driving Force for Assembly. To rationalize our experimental observations, we developed a physical (bead-spring) model [86][87][88][89] for the NC-linker mixtures based on our previous theoretical efforts 33,36 and recent studies of gelforming DNA nanostars 90 . We computed theoretical spinodal boundaries (model and theory details in Supporting Information) for the mixture with respect to the NC volume fraction NC and the linker-to-NC ratio Γ (Figure 4a) using first-order thermodynamic perturbation theory (TPT).…”
Section: Ligandmentioning
confidence: 99%
“…The lack of chemical details in the model is not a problem when looking for scaling laws or universal behaviour and the KG model has helped to clarify many aspects of the structure and dynamics of polymer chains in the immediate vicinity of surfaces 11,[20][21][22]24,25 . Svaneborg and co-authors 26,27 have recently showed that is it possible, by tuning the chain stiffness (i.e. the Kuhn length), to adapt a generic bead-and-spring polymer model to simulate melts of chemically-specific (at and above the Kuhn length) polymers.…”
Section: Introductionmentioning
confidence: 99%